Morphological Study of Layered Micro Deposits on Platinum Electrode During Potentiometric Titration of Hexadecyltrithiocarbonate with Transition Metal Ions - Raju, T.; Giribabu, K.; Narayanan, V. (Asian Journal of Chemistry, 2013)
In this work, we report the formation of multilayered micro deposits of M(DTTC)n on the platinum electrode during the potentiometric titration of hexadecyltrithiocarbonate (HDTTC) with cobalt(II), nickel(II) and copper(II) ions. The titration was carried out using universal buffer as the buffering agent in order to study the influence of the pH on the titrimetric analysis. In case of universal buffer, at higher pH (8-11) the recoveries of hexadecyltrithiocarbonate were found to be 80 %, which is an indicative of the formation of polynuclear complex. The formed deposits were studied by using scanning electron microscope and elemental diffraction analysis by X-rays (EDAX). An attempt was made to explain the formation of multilayers on to the platinum electrode.